Adapted Hedley fractionation for the analysis of inorganic phosphate in biogas digestate. (July 2021) - Dinkler, Konstantin; Li, Bowen; Guo, Jianbin; Hülsemann, Benedikt; Becker, Gero C.; Müller, Joachim; Oechsner, Hans
Graphical abstract: Highlights: Photometric spectra of Hedley fractionation extracts were analyzed for their peaks. Effect of drying on Hedley fractions was evaluated. The Hedley fractionation was adapted to be used with undried digestate. The accuracy of H2 O-P and NaHCO3 -P fractions is increased by the method adaptation. H2 O and NaHCO3 fractions represent 70% of inorganic phosphates in digestate. Abstract: The major share of phosphate in biogas digestate is inorganic. For optimized nutrient recovery, inorganic phosphate must be analyzed adequately. Therefore, the photometric spectra of extracts from Hedley fractionation were measured and analyzed for their peaks using the molybdenum blue method. The ideal wavelength was 709 nm. The lower calibration limit needed to be raised from 15 µg L −1 to 50 µg L −1 to avoid underestimation of phosphate concentration. Drying digestate before extraction increased H2 O-P by 78.4% and NaHCO3 -P by 44.9% compared to undried digestate. The filter paper of the filtration between extractions was added to the next extraction to avoid phosphate losses. This made it necessary to rinse the samples with 30 mL deionized H2 O after the H2 O extraction, with 60 mL NaHCO3 after NaHCO3 extraction and 60 mL NaOH after the NaOH extraction. Ultimately, the results showed that the phosphate concentration in extracts was independent of extraction time.